التظاهرات السريرية والتغيرات الشكليائية لدوالي الطرفين السفليين - أحمد عيسى; أحمد غانم (Latakia University Journal -Medical Sciences Series, 2013)
تصيب أوردة الدوالي حوالي10-59% من السكان. الدوالي انعكاس سريري للقصور المترقي في أوردة الطرفين السفليين. سبب القصور الوريدي هو الخلل البنيوي في جميع طبقات جدار الوريد. من هنا أهمية الدراسة الشكليائية والإحصائية لأوردة الطرفين السفليين ومقارنتها مع الطبيعي. أجرينا عمليات جراحية لدوالي 43 مريضاً، تمّ الفحص التشريحي المرضي لعينات الدوالي والأوردة الطبيعية المأخوذة من ثلاثة مرضى. متوسط أعمارهم 40,58 سنة. تمت الدراسة النسيجية والعيانية بأخذ مقاطع نسيجية مختلفة لأوردة الدوالي والأوردة الطبيعية، تم استعمال ملونات روتينية وخاصة من أجل كشف تغيرات العناصر التركيبية لجدار الوريد. توصلنا إلى الاستنتاجات والتوصيات التالية: وجود تغيرات مؤكدة نوعية وكمية في جميع العينات المرضية طالت عناصر النسيج الضام والألياف العضلية الملساء تتوزع في جميع طبقات جدار الوريد بشكل قطعي. ضرورة بدء علاج الدوالي أبكر ما يمكن من أجل تفادي تطورها والوصول إلى الاختلاطات. من المفيد محاولة دراسة العلاقة بين ظهور الدوالي والزمرة الدموية للمرضى. Varicose veins affects about 10-59% of the population. Varicose is a clinical reflection of the progressive failure in the veins of the lower limbs. Venous insufficiency is caused by structural imbalances in all layers of the wall of the vein, hence, the importance of morphologic and statistical studies of the varicose veins of the lower limbs and comparison with normal veins. We had surgery for varicose 43 patients. We examined all samples of varicose veins and normal veins of three patients with pathological studies. Average age was 40.58 years. The study was done macroscopically and microscopically, taking different histological sections of varicose and normal veins. Routine and special Dyes were used, in order to detect changes in the compositional elements of the vein wall. We reached the following conclusions and recommendations: the presence of certain changes in the quality and quantity in all pathologic samples along connective tissue elements and smooth muscle fibers, distributed in all layers of the wall of the vein definitively; the need to start treating varicose veins early as possible in order to avoid its development and access to complications; it is useful to attempt to study the relationship between the appearance of varicose veins and blood group of the patients.